Periodic Solutions to Nonlinear Second-Order Difference Equations with Two-Dimensional Kernel - Daniel Maroncelli (Mathematics, 2024)
In this work, we provide conditions for the existence of periodic solutions to nonlinear, second-order difference equations of the form <semantics>y(t+2)+by(t+1)+cy(t)=g(y(t))</semantics>, where b and c are real parameters, <semantics>c≠0</semantics>, and <semantics>g:R→R</semantics> is continuous.